Folk Song Arrangements in Music Ensembles to Promote National Culture at Santo Yosef School Surabaya - Kristiandri, Dhani; Dewi, Vivi Ervina; Sarjoko, Moh.; Suwahyono, Agus; Winarko, Joko (Universitas Negeri Medan, 2024)
In this study, the treatment provided is in the form of learning innovation by providing solutions that can invite students to love national culture again through folk song arrangements played in a music ensemble format. The research method used is mix method. The quantitative method uses experimental research type with one-group pretest-posttest design.The first activity carried out was the introduction of a folk song originating from East Java, namely the song